PENGARUH MOTIVASI DAN LINGKUNGAN KELUARGA TERHADAP MINAT BERWIRAUSAHA MAHASISWA (Studi Kasus Pada Mahasiswa Sekolah Tinggi Ilmu Sosial Dan Ilmu Politik Nurdin Hamzah Jambi) - Joli Anggraeni (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2019)
This study aims to determine the effect of variables of entrepreneurship motivation and family environment on student entrepreneur interest. (Case Study In High School Students Social Sciences And Political Sciences Nurdin Hamzah Jambi) The population in this study is a student of the College of Social and Political Science Nurdin Hamzah Jambi with 70 respondents. Data collection techniques used were questionnaires. Analyzer used in this research that is, test instrument consist of test of validity and reliability test, multiple linear regression analysis, f test and t test and coefficient of determination test. The overall analysis was calculated using the SPSS ver 22 program. The results of this study indicate that the motivation of entrepreneurship and family environment has a positive and significant effect on entrepreneur interest.